Sex-related characteristics of cerebral vein thrombosis: A secondary analysis of a multicenter international cohort study. Issue 196 (December 2020) - Porceddu, Enrica; Rezoagli, Emanuele; Poli, Daniela; Magliocca, Aurora; Scoditti, Umberto; Di Minno, Matteo Nicola Dario; De Stefano, Valerio; Siragusa, Sergio; Ageno, Walter; Dentali, Francesco; ,
Highlights: This is a secondary analysis stratified by sex of the CEVETIS that enrolled patients with a first event of cerebral vein thrombosis (CVT) The female-to-male distribution ratio of CVT in the CEVETIS population was 3:1 Infections, cranial trauma and unprovoked CVT were more frequent in males than in females VTE recurrence in other sites was twice as high in males compared to females. Venous thromboembolism (VTE) recurrence in other sites was twice as high in males compared to females A personal history of VTE was predictive of recurrence and poor outcome in females; cancer and MPN predicted poor outcome regardless of sex